Being Catholic in the contemporary Philippines: young people reinterpreting religion - Serrano Cornelio, Jayeel (Routledge religion in contemporary Asia series, 2016)
Young people and the changing face of Christianity -- Rethinking religious identity -- Researching youth and religious identity -- Will the real Catholic please stand up? -- Reinterpreting religion: creative Catholics and their reflexive spirituality -- Conservative yet liberal: creative Catholics and their moral attitudes -- Indwelt individualisation: creative Catholics and the emotional anthology of resources -- The isolated generation? -- Being Catholic